Pemberdayaan Masyarakat Dalam Pencegahan dan Pengelolaan Hipertensi Melalui Edukasi Gaya Hidup Sehat - Chusnul Zulaika; Eka Deviany Widyawaty; Nurmila Mutiah (Rena Cipta Mandiri, 2025)
This Community Service activity was held on September 21, 2025, at the Elderly Posyandu (Integrated Health Post for Elderly People) in Bibis Luhur Village, Banjarsari District, Surakarta, with 84 participants. The main challenges faced by the partners were the elderly's low level of knowledge regarding hypertension, the lack of regular blood pressure checks, and the lack of skills among cadres in conducting blood pressure checks and simple acupressure techniques. The activities included providing educational materials on hypertension, pre- and post-tests, blood pressure checks, and acupressure training at points PC6, HT7, and GB20. Results showed an increase in participant knowledge based on the post-test results, as well as in the cadres' ability to perform blood pressure checks independently. Participants were also able to practice acupressure and demonstrated high enthusiasm throughout the activity. This program resulted in increased community understanding, enhanced cadre skills, and a commitment to continue regular blood pressure monitoring by Posyandu cadres. This activity is expected to become a sustainable effort in preventing and managing hypertension in the community.